Association between antimicrobial use and antimicrobial resistance of Streptococcus uberis causing clinical mastitis - Martins, Larissa (2021)
It is unknown whether overuse of antimicrobials against clinical mastitis (CM) from Streptococcus uberis is associated with increased antimicrobial resistance (AMR). Therefore, the aim of this study was to evaluate the association between antimicrobial use (AMU) and AMR in relation to the Strep. uberis causing CM in dairy herds. A total of 83 Strep. uberis isolates were selected from a collection created during a previous study evaluating the epidemiology of CM in dairy herds (n = 17) of southeastern Brazil. For each case of CM identified on farm, the following information was recorded: cow's identification number, affected mammary quarter, date of CM diagnosis, antimicrobial commercial names, number of administrations, and descriptions of protocol changes during the treatment. Streptococcus uberis isolates were confirmed by conventional culture, MALDI-TOF mass spectrometry, and quantitative multiplex PCR analyses. Thus, a total of 8 antimicrobials commonly used for CM treatment were evaluated for antimicrobial activity against Strep. uberis isolates. The minimum inhibitory levels of antimicrobials were determined at the lowest concentrations able to inhibit 50 and 90%, respectively, of Strep. uberis isolates. Data related to the antibiotics used for treatment of CM was used to calculate the frequency of administered antimicrobials as the number of defined daily doses (DDD). The highest frequencies of resistant Strep. uberis were observed for erythromycin (80.7% resistant, R), tetracycline (R = 59%), and penicillin G (R = 57.8%), whereas against ceftiofur only 10.8% of Strep. uberis isolates were resistant, and only 1.2% of the Strep. uberis isolates were resistant to enrofloxacin. Regarding the evaluation of resistance for antimicrobial classes, the highest frequency was observed for macrolides (R = 80.7%; 19.3% susceptible, S). Additionally, a frequency of 18.7% of Strep. uberis isolates were resistant to cephalosporins (S = 81.3%), respectively. Further, 94% of Strep. uberis isolates were multiresistant; all these isolates presented resistance to at least 3 different antimicrobial classes. The overall monthly average of antimicrobial treatment incidence (ATI) among the 17 herds enrolled in the study was 23.7 DDD per 1,000 lactating dairy cows [standard deviation (SD) = 13.9], ranging from 5.0 to 55.4 DDD per 1,000 cows in lactation-day. Cephalosporins and penicillins were the most commonly used antimicrobial classes among the evaluated herds (n = 16; 94.1%), followed by tetracyclines (n = 15 herds; 88.2%), fluoroquinolones (n = 14; 82.3%), and sulfonamides (n = 14; 82.3%). The tetracycline class had the highest ATI mean (5.0 DDD per 1,000 lactating cow-days, SD = 5.8), followed by fluoroquinolones (4.7 DDD per 1,000 lactating cow-days, SD = 6.0) and cephalosporins (3.8 DDD per 1,000 lactating cow-days, SD = 6.0). The overall use of antimicrobials was associated with the resistance of Strep. uberis to the antimicrobial tetracycline.